2017
DOI: 10.35188/unu-wider/2017/369-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of routine essential care during childbirth: Clinical observations of uncomplicated births in Uttar Pradesh, India

Abstract: Objective To evaluate the quality of essential care during normal labour and childbirth in maternity facilities in Uttar Pradesh, India. Methods Between 26 May and 8 July 2015, we used clinical observations to assess care provision for 275 mother-neonate pairs at 26 hospitals. Data on 42 items of care were collected, summarized into 17 clinical practices and three aggregate scores and then weighted to obtain population-based estimates. We examined unadjusted differences in quality between the public and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
2
17
2
Order By: Relevance
“…38 Overall, we found that essential care at the time of birth, including active management of third stage of labour, was poor quality. 39 Although these findings do not address the casual effect of Matrika, they correlate well with the results we report here.…”
Section: Discussionsupporting
confidence: 83%
“…38 Overall, we found that essential care at the time of birth, including active management of third stage of labour, was poor quality. 39 Although these findings do not address the casual effect of Matrika, they correlate well with the results we report here.…”
Section: Discussionsupporting
confidence: 83%
“…However, the findings were not specific enough as whether the missing data were owing to misdiagnosis or gaps in record keeping. Nevertheless, the rates missed diagnosis were higher in our study compared to findings from a study in India [22].…”
Section: Plos Onecontrasting
confidence: 92%
“…Facilities with a moderate delivery load (20 -50 deliveries per month) and facilities with at least 70% of essential supplies available met a significantly more standards (Table 5). (26)(27)(28). However, the results are noteworthy as private health care facilities are generally perceived to be more efficient and provide better quality of services (29).…”
Section: Determinants Of Number Of Standards Metmentioning
confidence: 99%